Fire and grazing interaction in a subhumid grassland: effects on a dominant tussock grass - López-Mársico, Luis (2022)
1-Herbivory and fire are disturbances that reduce aboveground biomass in large areas. Some tussock grass-dominated grasslands need fire and grazing to be conserved in space and time. Asynchronous and patchy burning in a Uruguayan grassland region, temporarily reduces the cover of the unpalatable tussock grass Saccharum angustifolium. The aim of this study was to evaluate the effects of fire, grazing, and their interaction on structural and functional traits of a tussock grass, and its temporal dynamics in a subhumid grassland. 2-We set three blocks with four plots of 300 m2 each in a physiognomically homogeneous area dominated by S. angustifolium in a protected area. Each block presented the four possible combinations that emerged from the two levels of grazing (grazed/ungrazed) and burning (burned/unburned) factors. The experimental burning was carried out in the spring. Clump volume, number of flowering culms, Normalized Difference Vegetation Index of S. angustifolium, and soil variables were measured. 3- Burn characterization: Burning efficiency was 82%, burn intensity ranging from 178-610 KW.m-1, and the soil temperature increased 40% compared to pre-fire measurements. Temporal dynamic: The volume of S. angustifolium clumps decreased with fire, and the difference burned-unburned decreased with time. The burned-grazed treatment increased the number of S. angustifolium flowering culms. The NDVI of S. angustifolium clumps increased 50% with fire, and then decreased with time. Soil temperature and moisture were higher in burned treatments than unburned in some dates, and soil temperature was higher in grazed treatments than in ungrazed in some dates. Bulk density showed significant differences between burned and unburned plots, and through sampling dates for the 0-5 cm fraction. 4-Synthesis and applications. Our results provide new data in favor of the management practice carried out by livestock ranchers in Uruguayan grasslands dominated by S. angustifolium. The burning frequency is three-five years, and our data complement a model of alternative phases and states. Our results contribute to the evidence supporting that fire-directed grazing can maintain grasslands in a stable state. The conclusions drawn from our results constitute a useful contribution to the managers/authorities of the protected area and can be extrapolated to other grassland areas.